Influence of Plant Growth Stage and Temperature on Glyphosate Efficacy in Common Lambsquarters (Chenopodium album). (26th June 2018) - DeGreeff, Randy D.; Varanasi, Aruna V.; Dille, J. Anita; Peterson, Dallas E.; Jugulam, Mithila
Abstract: Plant growth stage and temperature influence the activity of glyphosate on common lambsquarters. A biotype of common lambsquarters in Dickinson County, KS (DK) was not controlled upon treatment with glyphosate in the field. In a greenhouse dose–response study, the DK biotype expressed 1.5-fold less sensitivity to glyphosate compared to a known susceptible biotype from Riley County, KS (RL). Common lambsquarters plants were treated at different growth stages (5 to 7, 10 to 12, 15 to 17, or 19 to 21 cm tall) with glyphosate at a field rate (840 g ae ha –1 ), and, regardless of the biotype, plants were more susceptible to glyphosate when they were 5 to 7 cm tall. Common lambsquarters plants were treated with glyphosate (840 g ae ha –1 ) after growing at different temperatures (25/15, 32.5/22.5, or 40/30 C day/night), and regardless of the biotype, plants were more susceptible to glyphosate when grown at 25/15 C. The results suggest that the DK biotype exhibits reduced sensitivity to glyphosate compared to the RL biotype, and glyphosate applied at field rate would be more effective on smaller common lambsquarters plants and at cooler temperatures. Common lambsquarters seedlings tend to emerge when temperatures are cooler, early in the spring relative to other summer annual weeds. Therefore, plants should be identified and treated earlier in the growing season for best efficacy with glyphosate.